Pengaruh Kepemilikan Manajerial dan Effective Tax Rate terhadap Kebijakan Dividen dengan Likuiditas sebagai Variabel Moderating - Nurul Rahmawati Putri; Wiwit Irawati (Universitas Swadaya Gunung Jati, 2019)
This study aims to determine the effect of Managerial Ownership, Effective Tax Rate on Dividend Policy with Liquidity as a moderating variable. Data collection is done on the Indonesia Stock Exchange through the website www.idx.co.id. This type of research is quantitative research. The sampling technique in this research was purposive sampling, with criteria for manufacturing companies listed on the Indonesia Stock Exchange (BEI) for five consecutive years, which produced 13 companies. The data analysis model used was Moderated Regression Analysis (MRA). The results of this study indicate that Managerial Ownership partially has no significant effect on Dividend Policy, the Effective Tax Rate partially has no significant effect on Dividend Policy, Liquidity does not moderate the Effect of Managerial Ownership on Dividend Policy and Liquidity successfully modifies the effect of Effective Tax Rate on Dividend Policy. According to the results of multiple linear regression tests Managerial Ownership and Effective Tax Rates simultaneously have no effect on Dividend PolicyKeywords: Managerial ownership; Effective tax rate; Liquidity; Dividend policy